An evaluation of the quality of customer service delivery offered by the East London public transport commuter rail service provider (operated by Metrorail) - Bosch, Colin (Rhodes University, Faculty of Commerce, Rhodes Business School, 2009)
The aim of this survey is to evaluate the quality of customer service delivery offered by the East London public transport commuter rail service provider Metrorail, a division of the state owned enterprise (SOE) PRASA. The former tolerant rail commuter has become increasingly frustrated at the ever-decreasing quality of rail service delivery. This is evidenced by increasing incidents of commuter arson to failed rail assets and the practice is considered to be a strategy to enforce the replacement of unreliable infrastructure and ineffective/reactive management controls. The objectives of the research are guided by three fundamental service quality indicators. In order to evaluate these indicators, the research focuses on whether the quality of customer services provided by Metrorail meets commuter expectations, whether commuters rank five dimensions of service quality differently and whether the level of service quality provided is perceived differently amongst the various demographic commuter segments. Service organizations which are highly interactive, labour-intensive, reliant on a number of service providers, required to perform at various locations and have high intensity/volume operations, will be susceptible to failure; Metrorail services fall into this category. The legacy of the apartheid era regime and strategy resulted in poor rail planning and underfunding. Commuter rail operations in South Africa are fraught with a myriad of inadequacies of the past that only now manifest. As a consequence, their ability to operate effectively and efficiently is impaired. The situation is further exacerbated by the global economic crisis of 2008 and the impact of constricted budget allocations by the State to all SOE's which could further impede the interventions and innovation required to improve service quality. The in-depth literature review provided sufficient information relating to a wide array of service organizations similar in nature to Metrorail. This information is translated into useable knowledge and recommendations from which Metrorail can benefit. The research methodology is clearly articulated and the data analysis ensures distinct findings which are discussed in the final chapter. The research undertaken identifies and prioritises the service quality attributes and dimensions that will require redress to improve overall service quality. The findings are clearly defined from which a set of recommendations are suggested.
Keywords: Railroads -- Customer services -- South Africa -- Eastern Cape; Transportation -- Customer services -- South Africa -- Eastern Cape; Railroads -- Quality control -- South Africa -- Eastern Cape